PENGARUH BOKASI ECENG GONDOK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH PADA TANAH PODSOLIK MERAH KUNING - Rahmat, Rahmat; Abdurrahman, Tatang; Patriani, Patriani (Jurnal Sains Pertanian Equator, 2018)
The research was aimed to study and determine the influence and dosage of the best water hyacinth compost on the growth and yield of shallot on red yellow podzolic soil. The research was carried out in Kalimas village, sub-district of Sungai Kakap, district of Kubu Raya from 20 July to 20 September 2017. This research used Completely Randomizied Design with five levels of water hyacinth compost treatment with five repetitions. Treatments consisted of m1=160g/polybag compost water hyacinth equivalent to 5 tons/ha, m2=320g/polybag compost water hyacinth equivalent to 10 tons/ha, m3=480g/polybag compost water hyacinth equivalent to 15 tons/ha, m4=640g/polybag compost water hyacinth equivalent to 20 tons/ha, m5=800g/polybag compost water hyacinth equivalent to 25 tons/ha. Observational variables were plant height, number of leaves, number of leaves/bulbs, number of bulbs, fresh weight /bulbs, fresh weight of bulbs, and dry weigh of bulbs per hill. The results showed that bengir water hyacinth compost had significant effect on plant height and leaf number at age 6 MST dan 8 MST, number of leaf/bulbs, number of bulbs and number of bulbs count, whereas in variable of plant height and number of leaf at age 2 MST and 4 MST, fresh weight/bulbs, fresh weight of bulbs and weight dry bulbs winds have no real effect. Based on the result of the research, it is concluded that the best dosage of hyacinth compost provision which can increase the growht and yield of shallot plant in red yellow podzolic soil is 640 g/polybag or equal to 20 ton/ha of organic material with yield of 5,38 ton/ha.Keywords : Red yellow podzolic soil, water hyacinth compost, shallot.